Bersih Pantai Sebagai Peningkatan Kesadaran Masyarakat dalam Kawasan Konservasi di Desa Paremas Kecamatan Jerowaru, Lombok Timur - Fitriani Mulyani, Laily; Marzuki, Muhammad; Sumsanto, Muhammad (Jurnal Pengabdian Perikanan Indonesia, 2023)
The increasing development of tourism in the Jerowaru Paremas conservation area has caused several problems, including environmental damage, environmental pollution and marine debris problems. One of the efforts that is expected to support coastal cleanliness is the active effort of the local community. The purpose of this activity is expected to be able to provide awareness of the cleanliness of the coastal environment for local communities and tourists as well as provide an understanding to the public that the waste produced has a negative impact on the development of biota and aquatic ecosystems. The method used in this clean-up activity is the observation, descriptive and participative method with the method approach used in counseling and training activities that are 'persuasive-educative' in nature, which are intended to provide knowledge and understanding in tackling coastal pollution. The clean-up activity was carried out and took place at Paremas Jerowaru, East Lombok Regency, which was attended by 200 participants from students, the community, fishermen and tourists in the Paremas Jerowaru Beach area, East Lombok Regency. This clean-up program can be organized properly and run smoothly in accordance with the activity plan that has been prepared. This clean-up activity can not only develop people's thinking patterns on preventing coastal environmental pollution, but also affect the cleanliness of the coastal environment to maintain conservation areas and also increase tourist attraction on the Paremas Jerowaru Beach, East Lombok.